Pengaruh Harapan Pelanggan dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Perumda Air Minum Wair Pu’an Maumere di Desa Lepo Lima - Yohanes Erwin; Yoseph Darius P. Rangga; Nunsio H. Meylano (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The background of this research was the current state of customer satisfactions at the Religional Public Company (PERUMDA) Air Minum Wair Pu’an Maumere in Lepo Lima Village, which has not been meeting customer expectations. This was evident from ongoing customer complaints, such as insufficient water discharge that failed to meet their needs or didn’t flow at all, as well as delays in addressing customer complaints. This research aimed to; (1) describe Customer Expectations, Service Quality and customer satisfaction; and analyze the significant impact of Customer Expectations and Service Quality on customer satisfaction. The population in this research was costumer of PERUMDA Air Minum Wair Pu’an Maumere in Lepo Lima Village, totaling 384 customers. Using the Slovin formula, the sample in this research was 100 customer. Data were collected through questionnaires and analyzed using the descriptive inferential method, namely multiple linear regression. Hypothesis testing was conducted through the F-test and T-test. The descriptive analysis results indicated that the variables of customer expectations, service quality, and customer satisfaction were well categorized. The result of the t-test statistics indicated that both customer expectation and sevice quality had a significant impact on customer satisfaction. Furthermore, the F-test statistics results demonstrated that boht customer expectations and service quality had a significant impact on customer satisfaction simultaneously. The determinant analysis revealed that customer expectations and service quality contributed 57.5% of customer satisfaction at PERUMDA Air Minum Wair Pu’an Maumere in Lepo Lima Village, with the remaining 42.5% influenced by factors outside the research variables.